2001
DOI: 10.1002/polb.10043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal history on the deformation and failure of polyimides

Abstract: Thermal-processing structure-property relationships for polyetherimide (PEI), poly(4,4Ј-oxydiphenylene pyromellitimide) (POPPI), and phenylethynyl-terminated imide (PETI-5) composite matrices are reported from a fundamental perspective. For thermoplastic PEI, deformation and failure depend primarily on free volume as evidenced by moisture-absorption, mechanical-property, and mass-density changes as a function of annealing. The deformation of POPPI can be divided into the following three regimes as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
(37 reference statements)
1
20
0
Order By: Relevance
“…Another important strategy for the improvement of polymers is annealing [34][35][36][37]: in that case the polymer is treated at a distinctly lower temperature, below the one needed for building covalent bonds between macromolecules and creating cross-links, but sufficiently high to induce irreversible changes of conformations or remove entanglements of macromolecular chains. In general, annealing leads to a reduction of free volume in the polymer [38].…”
Section: Introductionmentioning
confidence: 99%
“…Another important strategy for the improvement of polymers is annealing [34][35][36][37]: in that case the polymer is treated at a distinctly lower temperature, below the one needed for building covalent bonds between macromolecules and creating cross-links, but sufficiently high to induce irreversible changes of conformations or remove entanglements of macromolecular chains. In general, annealing leads to a reduction of free volume in the polymer [38].…”
Section: Introductionmentioning
confidence: 99%
“…Literature showed that PETI-5, with only a minimal increase in density (1234 kg/m 3 to 1335 kg/m 3 ), displayed a 35% increase in its elastic modulus, an 80.4% increase in its ultimate strength and was seen to be much more ductile at equal strain rates compared to 3900 (Lincoln et al 2001). Researchers also noted that PETI-5 was able to remain fairly ductile at much higher strain rates compared to the 3900.…”
Section: Polymer Matrix Compositesmentioning
confidence: 86%
“…This fact is very important in that solid control of the cooling process established a stable set of mechanical properties. Cooling rates of 1.1°C/m (Lincoln et al 2001) were shown to produce a more ductile polymer matrix with the highest recorded glass transition temperature and, therefore, the best thermal stability of all of the samples.…”
Section: Polymer Matrix Compositesmentioning
confidence: 99%
See 2 more Smart Citations